Spatial relationships of trees in middle taiga post-pyrogenic pine forest stands in the European North-East of Russia - Ivan N. Kutyavin; Alexei V. Manov (Journal of Forest Science, 2022)
Information on the structural organization of forest stands obtained on sample plots is the basis for long-term monitoring of post-fire pine forest structure and dynamics in the European North-East. These data can be used as a marker of native pine stands of the European taiga. Here, we studied vertical and horizontal structure in the post-pyrogenic pine forests of Vacciniosum, Vaccinioso-cladinosum and Myrtillosum site types in the boreal forest of the Komi Republic. The type of horizontal structure of uneven-aged forest stands changed with age from grouped to random one. Large trees were randomly distributed on the plot. We observed the weak aggregation of undergrowth trees (natural tree regeneration) in stands at distances of 2-6 m. Undergrowth individuals were characterized by group distribution at smaller distances than 1-2 m. Spatial relationships between large, small and codominant trees demonstrated random distribution in most cases. Undergrowth individuals did not show any competitive relations. However, we revealed a "taking off" effect between mature trees of pine and pine undergrowth. The direction of the displacement of tree crown centre projections relative to the bases of their trunks was ambiguous. The shift of the crown space towards the maximum solar radiation was detected in a thinned stand with old age and big size of trees. In other site types, no one-sided orientation of the tree crown development emerged.